La gestión educativa en el desempeño docente en la Unidad Educativa " San Francisco de Asís" Salcedo . Diseño de un plan de capacitación pedagógica. Período académico 2016 - 2017. - Yauri Remache, Alba Elizabeth (2016)
This research pretends to solve problems that determine how it impacts the Educational Management in the teacher performance of an Educative Unit in Salcedo – Ecuador, for which it has been raised like general objective maximize the Educational Management for improving the profile of teacher performance. The hypothesis that needs to clear consist in verify if the Educational Management will develop the teachers´ performance of the Educational Unit. The methodology used is based on a quantitative approach using the questionnaire like a principal instrument. As conclusions it has been achieved to determine that all the elements about the variables can be found described in the theory that based the research, as well as the existence of elements of the Educational management both inside and outside of the classroom that require to be reinforced and optimized. It is necessary to point that exist an important predisposition by educational teaching actors for the participation in the proposal generation for solving the problem set.